(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article explores the implementation of Integrated Language Teaching (ILT) in the classroom, a method combining listening, speaking, reading, and writing skills within a single educational framework. By emphasizing the interconnectedness of these skills, ILT mirrors real-life language use and fosters holistic language development. The article traces the evolution of language teaching methodologies, from the Grammar-Translation Method’s focus on rote learning of grammar and vocabulary to the Direct Method’s emphasis on oral communication and immersion. It highlights the mid-20th century Audio-Lingual Method, which prioritized repetition and drills but was criticized for neglecting meaningful communication and individual learner needs. The emergence of Technology-Enhanced Language Learning (TELL) revolutionized language instruction by integrating digital tools, offering immersive and engaging experiences. The article also delves into Content and Language Integrated Learning (CLIL), which combines subject matter instruction with language learning, addressing the dual need for subject competence and language proficiency. CLIL is noted for enhancing language skills more effectively by immersing students in subject-specific contexts, thus fostering practical language use and cultural understanding. The article underscores the benefits of ILT, particularly CLIL, in boosting student confidence, engagement, and motivation. By using a foreign language to learn subjects, students develop practical language skills and reduce language anxiety. The interactive and real-world focus of CLIL activities promotes a dynamic and supportive classroom environment, making learning more relevant and enriching. Ultimately, ILT offers a comprehensive and effective approach to language education, preparing learners for authentic communication and enhancing their overall educational experience.